A 5-Gb/s 66 dB CMOS Variable-Gain Amplifier With Reconfigurable DC-Offset Cancellation for Multi-Standard Applications - Zhiqing Liu; Yunqiu Wu; Chenxi Zhao; Johannes Benedikt; Kai Kang (IEEE Access)
This paper proposes a variable gain amplifier (VGA) with reconfigurable DC-offset cancellation (DCOC) for multi-standard applications. In this design, a cell-based design method and some bandwidth extension technologies are adopted to achieve a high data rate and a wide gain control range simultaneously. In addition, the DCOC having a tunable lower-cutoff frequency can make an optimum compromise between BER and SNR according to the specified baseband standard. The measurements show that the VGA achieves a gain control range from −6 dB to 60 dB, a bandwidth beyond 3 GHz, and a tunable lower-cutoff frequency from 0 to 300 kHz. When entering a 223−1 pseudo-random bit sequence signal at 5 Gb/s, the VGA consumes 17 mW from a 1.2-V supply and the output data peak-to-peak jitter is less than 40 ps. The VGA is fabricated in a 90-nm CMOS process with a chip size (including all pads) of $0.52×0.5$ mm2.